2023
DOI: 10.1109/jbhi.2022.3229211
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Analysis of Compound Muscle Action Potential Scan: Staircase Function Fitting and StairFit Motor Unit Number Estimation

Abstract: Compound muscle action potential (CMAP) scan provides a detailed stimulus-response curve for examination of neuromuscular disease. The objective of the study is to develop a novel CMAP scan analysis to extract motor unit number estimation (MUNE) and other physiological or diagnostic information. A staircase function was used as the basic mathematical model of the CMAP scan. An optimal staircase function fitting model was estimated for each given number of motor units, and the fitting model with the minimum num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…23 MUNE in chronic SCI has also recovered to control values for the tibialis anterior, abductor hallucis, and extensor digitorum brevis. 25 Conversely, other studies found that MUNE in chronic SCI remained lower compared to controls in the tibialis anterior, 25,26 abductor hallucis, 26 extensor digitorum brevis, 25 first dorsal interosseous, [27][28][29][30] thenar, 27,31,32 and hypothenar muscles 33 (Figure 1). Interestingly, some have hypothesized that motor unit numbers may decrease over time after SCI due to transsynaptic degeneration, 8,23 but this hypothesis has not been corroborated by the MUNE.…”
Section: Motor Unit Number Estimationmentioning
confidence: 90%
“…23 MUNE in chronic SCI has also recovered to control values for the tibialis anterior, abductor hallucis, and extensor digitorum brevis. 25 Conversely, other studies found that MUNE in chronic SCI remained lower compared to controls in the tibialis anterior, 25,26 abductor hallucis, 26 extensor digitorum brevis, 25 first dorsal interosseous, [27][28][29][30] thenar, 27,31,32 and hypothenar muscles 33 (Figure 1). Interestingly, some have hypothesized that motor unit numbers may decrease over time after SCI due to transsynaptic degeneration, 8,23 but this hypothesis has not been corroborated by the MUNE.…”
Section: Motor Unit Number Estimationmentioning
confidence: 90%
“…CMAP scan processing: To evaluate motor unit number alteration, the CMAP scan data was processed using three different methods, namely MScanFit MUNE (Bostock, 2016;Jacobsen et al, 2018), StairFit MUNE (Chen et al, 2023) and STEPIX (Nandedkar et al, 2022). The default setting of model options (relative spread RS% = 2, deleted units <25 μV applied, set number of units to 20) was used when implementing MScanFit MUNE.…”
Section: Cmap Scan Examinationmentioning
confidence: 99%
“…In addition to routine nerve conduction studies, compound muscle action potential (CMAP) scans were recorded before and after the treatment (Visser and Blok, 2009). Motor unit number changes were examined using different CMAP processing methods including MScanFit motor unit number estimation (MUNE) (Bostock, 2016;Jacobsen et al, 2018), StairFit MUNE (Chen et al, 2023), and step index (STEPIX) (Nandedkar et al, 2022). To the best of our knowledge, this is the first CMAP scan study in CTS population.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, compound muscle action potential (CMAP) scan aims to gradually activate/deactivate all motor units by applying hundreds of transcutaneous stimuli to the motor nerve across a wide range of intensities ( Blok et al, 2007 ). Compared with traditional MUNE methods, CMAP scan is less biased to the sampling of motor units, and various methods have been developed to process CMAP scan for examination of neuromuscular disorders ( Sleutjes et al, 2014 ; Nandedkar et al, 2022 ; Chen et al, 2023a , b ; Lu et al, 2023b ). Of particular note, Bostock proposed a model-based MUNE algorithm named MScanFit, which estimates the number of motor units by fitting the detailed stimulus–response curve recorded from a CMAP scan ( Bostock, 2016 ).…”
Section: Introductionmentioning
confidence: 99%